2013
DOI: 10.1016/j.jcot.2013.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Hamstring graft size and anthropometry in south Indian population

Abstract: a b s t r a c tBackground and Aim: The role of anthropometric measurements in the prediction of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
25
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 25 publications
4
25
1
Order By: Relevance
“…The ability to predict the length of the hamstring graft preoperatively is of great importance and may help the surgeon in the decision to achieve an acceptable diameter for the autograft in ACL reconstruction. This study demonstrated a positive correlation between the patient height and thigh length with semitendinosus and gracilis graft length; this positive correlation was also reported in previous literatures [14][15][16][17].…”
Section: Discussionsupporting
confidence: 90%
“…The ability to predict the length of the hamstring graft preoperatively is of great importance and may help the surgeon in the decision to achieve an acceptable diameter for the autograft in ACL reconstruction. This study demonstrated a positive correlation between the patient height and thigh length with semitendinosus and gracilis graft length; this positive correlation was also reported in previous literatures [14][15][16][17].…”
Section: Discussionsupporting
confidence: 90%
“…The average length of the ST tendon in this study was 29.80 cm and over 67% of our population had a ST tendon whose length was at least 28 cm. When compared to reports from Chinese, Austrian and Indian populations, our sample population had a longer ST tendon (18)(19)(20). Greeks, on the other hand, are reported to have longer tendons than observed in our sample population as summarized in table 3 (9).…”
Section: Discussioncontrasting
confidence: 45%
“…Hamstring tendon length becomes important when (1) triplicated tendon is required in order to increase graft diameter, (2) longer graft length is needed for augmenting fixation by a post, (3) single bundle augmentation is planned using only one of the hamstring tendons, (4) combined reconstructions for multi-ligament injury is to be considered, or (5) double bundle ACL reconstruction is required [22][23][24][25]. Few studies have correlated anthropometric parameters to length of hamstring tendons with ACL graft length of about 8-10 cm (4 cm intra-articular and 2-3 cm on either side in femur and tibia tunnel) being necessary for stable fixation during surgery and good tendon to bone contact for healing [12,13,22,23].…”
Section: Mean Of the Actual And Predicted Graft Diameter (Mm)mentioning
confidence: 99%
“…Few studies have correlated anthropometric parameters to length of hamstring tendons with ACL graft length of about 8-10 cm (4 cm intra-articular and 2-3 cm on either side in femur and tibia tunnel) being necessary for stable fixation during surgery and good tendon to bone contact for healing [12,13,22,23]. To increase diameter of graft triplication of either tendon may be required and length of 24-30 cm of harvested tendons is necessary.…”
Section: Mean Of the Actual And Predicted Graft Diameter (Mm)mentioning
confidence: 99%
See 1 more Smart Citation